Association between Vitamin D and Knee Osteoarthritis: A PRISMA-Compliant Meta-analysis - Yu, Yinghao; Liu, Dongcheng; Feng, Dehong; Zhao, Jijun (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Background Previous investigations showed inconsistent results for associations between vitamin D and knee osteoarthritis (OA). The present study aimed to make a systematic review and meta-analysis for the association between vitamin D and knee OA.Methods We systematically searched for articles published in the databases PubMed, Web of Science, EMBASE, Medline, and Google Scholar through July 2019. All statistical analyses were made using STATA 12.0 software. The Q test and I2 were applied to examine heterogeneities between studies.Results The study indicated that there were no significant associations between serum levels of 25-hydroxy (OH) vitamin D and prevalence, incidence or progression of knee radiographic OA (ROA), and joint space narrowing (JSN). However, a subgroup study showed significant associations of low vitamin D levels with the progression of knee OA. Additionally, the present study showed no significant effect of vitamin D supplementation on knee OA.Conclusions The results do not support that serum levels of 25(OH) vitamin D are associated with the risks of knee OA, except perhaps with progression of knee OA. In addition, vitamin D supplementation may not have a clinically significant effect on pain control or structure (tibial cartilage volume and JSW) progression in patients with knee OA. Longer-term clinical trials are essential to explore the effect of vitamin D supplementation on knee OA.
Keywords: knee osteoarthritis; meta-analysis; vitamin D; 25-hydroxy vitamin D